NOMINAL KAŊ FORM IN BASSE MANDINKA – ITS COGNITIVE MAPPING AND TAXONOMICAL STATUS (PART 1) - Andrason, Alexander (Lingua Posnaniensis, 2013)
The present study, divided into a series of two papers, provides a detailed empirical description and cognitive-grammaticalization analysis of the meaning of a Mandinka verbal expression compounded of the non-verbal predicator be ‘be’, a verbal noun expressing a given action and the postposition kaŋ ‘on, at’ (so-called the Nominal KAŊ form). Method: The author follows the cognitive approach to verbal semantics which consists first of determining the exact range of contextually induced senses and next of unifying such values into a consistent map based upon certain diachronic universals or grammaticalization paths. Results: The synchronic inventory of senses of the Nominal KAŊ form (i.e. progressive, continuous, progressive-iterative, iterative, habitual and durative values) shows that this construction can be mapped using the imperfective path as a template of chaining. This mapping, hypothesized on the ground of synchronic semantic evidence and typological diachronic laws, is next corroborated by the structural properties of the Nominal KAŊ locution, especially by its locative and nominal character. Conclusion: All the evidence enables the author to semantically define the NomKAŊ form as a nonadvanced imperfective path. Part 1: In the first article of the series, the author deals with methodological issues and with an empirical study where he determines the precise extent of the semantic potential of the Nominal KAŊ form.